THE IMPORTANCE OF S I L L IN READING COMPREHENSION - Zulkifli; Herman (Politeknik Negeri Sriwijaya, 2025)
Teachers’ success in teaching and learning process depends on how she/he propel his/her students to learn. There are two contradictory points of view. On one hand, teachers want their students to become active and self-confident in learning, while on the other hand, students consider that the process of teaching and learning activities is the teachers’ responsibility. This often makes students passive, and they just sit and wait for whatever the teachers are going to give them. The teacher has responsibilities not only for giving the input of transferring knowledge or competence, but also teaching them how to study. The purpose of writing this paper is to provide an alternative to improving the process of teaching and learning activities. It is based on the observation that reading comprehension is still at a low level, and it should be improved. The improvement can be done through more exposure to learning strategies. Students’ self-consciousness on how important learning strategies are makes students to autonomous. It is suggested to do more seminars and research on language learning strategies for making the improve of teaching and learning quality and to gain more knowledge and experience.